Clinical management and burden of cytomegalovirus in D+/R-Kidney transplant recipients in Canada - Gill, John; House, Andrew A.; Chagla, Zain; Tchervenkov, Jean; Kim, S. Joseph; Vinson, Amanda; Cervera, Carlos; Keown, Paul A.; Sun, Sonia Lai Wing; Khoury, Christina; Ghakis, Christiane (Frontiers in Immunology, 2025)
PurposeTo document prophylactic practices, infection patterns, and disease burden to inform strategies for CMV management in high-risk kidney transplant recipients.MethodsA retrospective cohort of 311 consecutive CMV D+/R- kidney recipients were enrolled from 7 Canadian programs over 4 years (2018-2021) to provide data on demographic, clinical, therapeutic and health resource use during the 1st year post-transplant.ResultsThemedian age was 58 (46, 67) years, 69% were male, and 53% were White. Diabetes was the principal cause of kidney failure (19%). 208 (69%) received a deceased donor graft; 76 (24%) had ATG induction, and 84% had maintenance therapy with tacrolimus and MMF/MPA ± prednisone. All received antiviral prophylaxis, 90% with valganciclovir, for a median of 180 days. 106 (34%) developed CMV viremia (median peak viral load 14,224 IU/ml) at a median of 218 days, of whom 46 (43%) had CMV disease and 15 (14%) had recurrent infection. Myelotoxicity occurred in 121 (39%) patients at a median of 88 days, lasting a median of 30 days. Opportunistic infections occurred in 119 patients (38%) at a median of 53 days. 141 patients (45%) were hospitalized, 50 (16%) more than once. 20 patients (6%) had biopsy-confirmed rejection, and 293 (94%) were alive with a functioning graft at 1 year.ConclusionCurrent prophylaxis strategies fail to prevent CMV infection in 34% of high-risk patients. Myelotoxicity, opportunistic infection, reduced immunosuppression, and hospitalization remain common and serious complications. More effective and less toxic personalized treatment strategies are required to minimize these risks and burdens.